Development of spray freezer for production of freeze granulations - B, DARSHAN M; KAR, ABHIJIT; MOHAPATRA, DEBABANDYA (The Indian Journal of Agricultural Sciences, 2015)
Spray freezer is an essential component of spray freeze drying (SFD) technique to produce microspheres during encapsulation. In this study, a lab scale spray freezer unit was developed to produce freeze granulations, which could be used for encapsulation of bio-pigments and other useful bio-active compounds. The components of spray freezer were spray nozzle, freezing chamber, magnetic stirrer, feed reservoir, homogenizer, peristaltic pump, air compressor, liquid nitrogen tank and hose fittings. The maltodextrin ‘MD’ solution (10%) was atomized into liquid nitrogen using spray freezer to produce freeze granulations and these granulations were freeze dried to obtain spray freeze dried maltodextrin (SFDMD) particles. The produced SFDMD particles were characterized and compared with classical freeze dried maltodextrin (FDMD) particles to evaluate the performance of spray freezing unit. The drying period for producing maltodextrin granules in SFD and freeze drying (FD) technique was between 12 to 24 and 36 to 48 hr, and their % moisture absorption was found to be 2.37 and 2.17%, respectively. The SFD technique produced microspheres of maltodextrin with particle size ranging from 2 to 60 μm, whereas FD technique produced irregular macro-size flakes. The morphological studies revealed that SFD microstructure particles had smooth surface and freeze dried particles had rough surface; however, porous appearance was observed in both samples. There were no significant differences in colour values; however, the flow properties of SFDMD particles were relatively better than FDMD particles. The developed spray freezer can be used for production of freeze granulations during SFD technique.